Nurturing cultural awareness via e-mail exchanges in an english as a second language (ESL) reading writing classroom / Sheela Paramasivam, Kaarthiyainy Supramaniam and Geraldine de Mello - Paramasivam, Sheela; Supramaniam, Kaarthiyainy; de Mello, Geraldine (Universiti Teknologi MARA Cawangan Pahang, 2008)
In this era of globalisation, it is necessary for students to be sensitised of towards other cultures around the world, and this could be done in the ESL classroom. This paper shows how modern technology such as email, can become a powerful tool and could be used to bridge language learning and cultures. This project involves a group of Thai and Malaysian students who were instructed to email each other to gather information on various themes such as religion, places of interest, food and lifestyle. Throughout the project, they were encouraged to share their experiences in groups and in writing reports. At the end of the project, questionnaires with closed- and open-ended questions were distributed to Malaysian students to get their feedback on the email project as well as their language learning experience. Assessment was also done on their reports. It could be summed that they overcame their anxiety and discovered that learning English was more than just mastering grammar. More importantly, it fostered the perception that learning English was fun and meaningful, no matter what culture they belonged to.